Tamanho de amostra de caracteres de genótipos de soja Sample size of the characters in soybeans genotypes - Alberto Cargnelutti Filho; Dilson Henrique Ramos Evangelista; Elaine Cristine Piffer Gonçalves; Lindolfo Storck (Ciência Rural, 2009)
O objetivo deste trabalho foi estimar o tamanho de amostra necessária para avaliar caracteres de genótipos de soja (Glycine max L.) e verificar a variabilidade do tamanho de amostra entre genótipos e entre experimentos. Para tanto, 28 genótipos de soja foram avaliados em cinco experimentos conduzidos em Jaboticabal, Estado de São Paulo (latitude 21°15'22"S, longitude 48°18'18" W e 595m de altitude), nos anos agrícolas de 2002 a 2005. Foi utilizado o delineamento de blocos ao acaso, com três repetições, e foram avaliados os caracteres altura de planta na maturação e de inserção de primeira vagem, número de nós por planta, de ramos por planta e de vagens por planta em seis plantas amostradas aleatoriamente na parcela. Há variabilidade da estimativa do tamanho de amostra entre genótipos quanto ao número de nós por planta e entre experimentos quanto à altura de planta na maturação, ao número de nós por planta, de ramos por planta e de vagens por planta. Para melhorar a precisão da avaliação de caracteres em plantas de soja, deve-se usar maior número de repetições e, pelo menos, 12 plantas por unidade experimental. The aim of this research was to determine the sample size of characters in different soybeans (Glycine max L.) genotypes and to verify its variability among genotypes and experiments. Twenty-eight soybeans genotypes were evaluated in five experiments conducted in Jaboticabal, São Paulo State, Brazil (latitude 21°15'22"S, longitude 48°18'18" W, altitude 595m), in agricultural years from 2002 to 2005. Randomized blocks design with three repetitions was installed to evaluate the following characters: plant height at maturity, height of first pod insertion, number of nodes per plant, number of branches per plant and number of pods per plant, in six plants sampled at random in each plot. It was found variability in the sample size among genotypes in relation to the number of nodes per plant. When the five experiments were compared, results also show variability of the sample size in relation to plant height at maturity, number of nodes per plant, number of branches per plant and number of pods per plant. To improve the experimental precision in the evaluation of characters in soybeans plants it is recommended to increase the number of repetitions and use, at least, twelve plants per plot.